Governance and Conflict in the Sahel’s ‘Ungoverned Space’ - Clionadh Raleigh; Caitriona Dowd (Stability : International Journal of Security and Development, 2013)
This article concerns governance and violence rates across the ‘ungoverned’ spaces of the African Sahel. We consider how the dominant narrative for Africa generally, and the Sahel specifically, ‘securitizes’ space, and presents poverty, underdevelopment, and ‘ungoverned’ spaces as security threats to be addressed (Abrahamsen 2005; Keenan 2008). We argue that the terms ‘failed’ and ‘ungoverned’ have become coterminous and common because they benefit various state and international powers within and across the Sahel, who avoid responsibility for the geo-political and economic processes within these spaces. Not only does the term ‘ungoverned’ obscure the actual practices of power within large states with significant under-populated spaces, but it wrongly assumes and accuses those within that space of being more likely to engage in forms of violence that are destabilizing to state structures and external interests. Actual practices of power across the Sahel reveal that large Sahelian states differ significantly in their types of governance, violence rates and trajectories, activities of opposition groups, and long-term prospects for peace.